A Central Role for Triacylglycerol in Membrane Lipid Breakdown, Fatty Acid β-Oxidation, and Plant Survival under Extended Darkness . Issue 3 (1st June 2017) - Fan, Jilian; Yu, Linhui; Xu, Changcheng
Abstract : Triacylglycerol is a key intermediate in membrane lipid breakdown and fatty acid β-oxidation, and blocking triacylglycerol hydrolysis reduces oxidative stress and enhances plant survival under extended darkness. Abstract: Neutral lipid metabolism is a key aspect of intracellular homeostasis and energy balance and plays a vital role in cell survival under adverse conditions, including nutrient deprivation in yeast and mammals, but the role of triacylglycerol (TAG ) metabolism in plant stress response remains largely unknown. By thoroughly characterizing mutants defective in SUGAR-DEPENDENT1 (SDP1) triacylglycerol lipase or PEROXISOMAL ABC TRANSPORTER 1 (PXA1), here we show that TAG is a key intermediate in the mobilization of fatty acids from membrane lipids for peroxisomal β-oxidation under prolonged dark treatment. Disruption of SDP1 increased TAG accumulation in cytosolic lipid droplets and markedly enhanced plant tolerance to extended darkness. We demonstrate that blocking TAG hydrolysis enhances plant tolerance to dark treatment via two distinct mechanisms. In pxa1 mutants, in which free fatty acids accumulated rapidly under extended darkness, SDP1 disruption resulted in a marked decrease in levels of cytotoxic lipid intermediates such as free fatty acids and phosphatidic acid, suggesting a buffer function of TAG accumulation against lipotoxicity under fatty acid overload. In the wild type, in which free fatty acids remained low and unchanged under dark treatment, disruption of SDP1 caused a decrease in reactive oxygen species production and hence the level of lipid peroxidation, indicating a role of TAG in protection against oxidative damage. Overall, our findings reveal a crucial role for TAG metabolism in membrane lipid breakdown, fatty acid turnover, and plant survival under extended darkness.